Specific bacterial microbiome enhances the sexual reproduction and auxospore production of the marine diatom, Odontella - Marilou P. Sison-Mangus; Michael W. Kempnich; Monica Appiano; Sanjin Mehic; Terril Yazzie (PLoS ONE, 2022)
Auxospore production is a sexual reproductive strategy by diatoms to re-attain normal size after the size-reducing effect of clonal reproduction. Aside from the minimum size threshold used as a sex clock by diatoms, the environmental or chemical triggers that can induce sex in diatoms are still not well understood. Here we investigated the influence of six marine bacteria from five families on the production of sexual cells and auxospores of the ubiquitous marine polar centric diatom, Odontella sp. Microbiome association and co-occurrence with the diatom in culture and in nature were investigated using 16S rRNA amplicon sequencing. Indole acetic acid (IAA) secretion, a phytohormone that regulates plants’ growth and sexual development, was explored as a potential inducer of sexual reproduction in Odontella and compared between bacterial associates. We found that Odontella co-cultured with Flavobacteriaceae (Polaribacter and Cellulophaga) have significantly more sexual cells and auxospores than bacteria-free Odontella and Odontella co-cultured with other bacteria from Vibrionaceae (Vibrio), Pseudoalteromonadaceae (Pseudoalteromonas), Rhodobacteraceae (Sulfitobacter), or Planococcaceae (Planococcus) family. Differences in IAA secretion were observed between bacterial isolates, but this did not correspond consistently with the diatom’s clonal growth or production of sexual cells and auxospores. Microbiome composition survey of Odontella cultures showed that the diatom harbors homologous sequences of the four bacterial isolates at varying proportions, with Sulfitobacter and Polaribacter at high abundances. Microbiome surveys at Santa Cruz Wharf, Monterey Bay, from 2014–2015 showed that Odontella abundance is positively correlated with Flavobacteriaceae and Rhodobacteraceae abundances. Our study demonstrates that specific members of the diatom microbiome can enhance the host’s sexual reproduction, with the interkingdom interaction driven by partner compatibility and long-term association. Sex-enhancing bacteria may even be needed by the diatom host to carry out the optimal inducement of sex under normal conditions, allowing for size restitution and maintaining genetic diversity in culture and in nature.